Analysis of the biochemical role of Lys‐11 in polyubiquitin chain formation using quantitative mass spectrometry. (13th December 2012) - Jung, Jin Woo; Bae, Sung Jun; Kang, Gum‐Yong; Kim, Kyun‐Hwan; Yeo, Woon‐Seok; Park, Sang‐Hyun; Seol, Jae Hong; Yi, Eugene C.; Kim, Kwang Pyo
<x xml:space="preserve">Abstract</x> RATIONALE Protein ubiquitination plays a critical role in regulating many cellular events, such as protein localization and stability, cellular signal transduction and DNA repair. Recent studies have shown that polyubiquitin (polyUb) chains elongate through heterogeneous isopeptide linkages to K11, K29, K48 and K63. In this study we have investigated the usage of isopeptide linkages of polyUb chains in different molecular weight regions by using quantitative mass spectrometry. METHODS Recombinant Chfr protein was autoubiquitinated by E1 enzyme, E2 enzyme UbcH5 and ubiquitin (WT Ub, K11R Ub, K48R Ub and K63R Ub) in vitro, and different molecular weight regions of ubiquitinated Chfr were then subjected to liquid chromatography coupled with tandem mass spectrometry (LC/MS/MS) following sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS‐PAGE) and in‐gel digestion. RESULTS Absolute QUantitative Analysis (AQUA) of polyUb chain formation with wild‐type (WT) and point mutants of ubiquitin was performed, and the results suggested that the K11 polyUb chain was most frequently used in the high ubiquitin conjugates of WT Ub. Furthermore, the extent of polyUb chain formation with K11R Ub was decreased about 10‐fold compared to polyUb chain formation with WT Ub through the entire molecular weight region. The present study suggests that the linkage through K11 plays crucial roles in polyUb chain formation. CONCLUSIONS Topologies of polyUb chains in the low and high Ub conjugates were studied using mass spectrometry. K48 and K63 were the primary ubiquitination sites of the low molecular weight Ub conjugates, whereas K11 was the critical site of polyUb chain formation in high molecular weight Ub conjugates. Copyright © 2012 John Wiley & Sons, Ltd.